MODERN METHODS OF TEACHING ENGLISH (Web of Teachers: Inderscience Research, 2023)
This article analyzes the opinions and scientific views of scientists and pedagogues regarding the use of new pedagogical methods in teaching English, in particular, interactive methods and the scientific-theoretical aspects of the factors that arouse students' interest in learning this language, and their subjective attitude to them attitude expressed.